IMPROVING STUDENTS' SPEAKING ABILITY BY USING MIND MAPPING TECHNIQUE AT THE ELEVENTH GRADE OF SMA NEGERI 6 KOTA BENGKULU - Stepy Theresia Kurnia Putri; Nadrah; Hanura Febriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to explain the implementation of the Mind Mapping technique in improving students' speaking ability. The research employed a collaborative Classroom Action Research (CAR) design following the Kemmis and McTaggart (2014) model, conducted in two cycles with 36 students of class XI F. Data were collected through speaking tests, field notes, and interviews, and assessed using Heaton's (1988) rubric across four components: fluency, accuracy, pronunciation, and comprehensibility. The success criterion required at least 70% of students to achieve a minimum score of 70. The findings revealed significant improvement in students' speaking ability after the implementation of the Mind Mapping technique. In Cycle 1, the mean score was 63.6 with only 30.6% of students achieving the KKM. After implementing revisions in Cycle 2, such as the use of dictionaries, more varied topics, and additional individual practice time, the mean score increased to 75.1 with 86.1% of students achieving the KKM. All four speaking components showed improvement, with comprehensibility showing the most significant increase. This study concludes that the Mind Mapping technique is effective in improving students' speaking ability by helping them organize ideas visually, reducing cognitive load and anxiety, and providing a structured thinking framework.